2011
DOI: 10.2174/187231211794455244
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Effects of Nitric Oxide Donors on the Biliary Efflux Transporters in Isolated Perfused Rat Livers: Nitric Oxide-Independent Inhibition of ABC Transporters by Sodium Nitroprusside

Abstract: Rhodamine 123 (RH-123) and its glucuronidated metabolite (RH-Glu) are excreted into the bile via the ABC efflux transporters P-glycoprotein (P-gp) and multidrug resistance-related protein type 2 (Mrp2), respectively. In this study, we investigated the short-term (2 h) effects of a low or high concentration of nitric oxide (NO) donors sodium nitroprusside (SNP) and isosorbide dinitrate (ISDN) on the hepatobiliary disposition of RH-123 and its metabolite in an isolated perfused rat liver model. Additionally, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…In addition, the specific NO scavenger PTIO did not reverse the SNPinduced alteration of P-gp function, indicating that the effect of SNP on P-gp function occurred via an NO-independent mechanism [29] . This result agreed with previous studies performed in isolated perfused rat livers [32] . Furthermore, a significant increase in intracellular ROS (iROS) and RNS (iRNS) in Caco-2 cells was observed at early stages of SNP exposure, which indicated that iROS and iRNS were involved in the SNP-induced impairment of P-gp function.…”
Section: Discussionsupporting
confidence: 94%
“…In addition, the specific NO scavenger PTIO did not reverse the SNPinduced alteration of P-gp function, indicating that the effect of SNP on P-gp function occurred via an NO-independent mechanism [29] . This result agreed with previous studies performed in isolated perfused rat livers [32] . Furthermore, a significant increase in intracellular ROS (iROS) and RNS (iRNS) in Caco-2 cells was observed at early stages of SNP exposure, which indicated that iROS and iRNS were involved in the SNP-induced impairment of P-gp function.…”
Section: Discussionsupporting
confidence: 94%
“…1 The mechanisms associated with multidrug resistance in cancer have been widely explored, and chemotherapy-induced upregulation of P-glycoprotein is considered the major event in establishing multidrug resistance in cancer cells. 2 Much research attention has been focused on the discovery and development of agents that can inhibit P-glycoprotein with high efficiency and low toxicity.…”
Section: Introductionmentioning
confidence: 99%